2008
DOI: 10.1108/13673270810852368
|View full text |Cite
|
Sign up to set email alerts
|

Organizational characteristics as prescriptive factors of knowledge management initiatives

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 15 publications
(18 reference statements)
1
73
0
2
Order By: Relevance
“…In addition, organizational climate and organizational structure have been recognized as shaping KM (Chen & Huang, 2007). In fact, previous research has shown that the organization of the firm -such as its structure, membership, relationships, and strategy -constrain and influence the nature of KM (Magnier-Watanabe & Senoo, 2008). There has, however, been little research on how all these factors taken together affect KM, especially in the context of the global business market.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, organizational climate and organizational structure have been recognized as shaping KM (Chen & Huang, 2007). In fact, previous research has shown that the organization of the firm -such as its structure, membership, relationships, and strategy -constrain and influence the nature of KM (Magnier-Watanabe & Senoo, 2008). There has, however, been little research on how all these factors taken together affect KM, especially in the context of the global business market.…”
Section: Introductionmentioning
confidence: 99%
“…KM is the essential speculation which grants to manage and share the knowledge within an organization, and to create new collective knowledge of the group [33]. In terms of most efficient method, KM can be defined as the process for acquiring, storing, diffusing and implementing the organizational boundaries between the tacit and explicit knowledge [19].…”
Section: Knowledge Management (Km)mentioning
confidence: 99%
“…Besides, Knowledge management can be defined four dimensions as acquisition, storage, dissemination and implementation of corporate objectives [19]. Because KM is a concept in which an enterprise consciously gathers, organizes, shares, and analyzes its knowledge in terms of resources [29].…”
Section: Knowledge Management (Km)mentioning
confidence: 99%
“…MagnierWatanabe and Senoo (2008) in their definition of KM place emphasis on the knowledge value chain (Magnier-Watanabe, 2011). Magnier-Watanabe and Senoo (2008) state that KM is the process of acquiring, storing, sharing, disseminating and applying knowledge both inside and outside the organization, with the goal of efficiently meeting corporate objectives. The effective use of KM helps organizations to improve the quality of their decision-making and thus, to reduce costs and increase efficiency and monitoring capabilities (Ferreira, Faria, Azevedo, & Marques, 2016;Heisig et al, 2016;Kinicki & Kreitner, 2008).…”
Section: Knowledge Management Frameworkmentioning
confidence: 99%